Alleviation of doxorubicin–induced hepatorenal toxicities with sesamin via the suppression of oxidative stress. (November 2016) - Guo, H; Liu, Y; Wang, L; Zhang, G; Su, S; Zhang, R; Zhang, J; Li, A; Shang, C; Bi, B; Li, Z
Hepatorenal toxicities are an important side effect of anthracycline antibiotics. The objective of this study was to determine whether sesamin (Ses) protects against acute doxorubicin (DOX)-induced hepatorenal toxicities. Rats received daily treatment with either 0.5% carboxymethylcellulose (10 mL/kg) or Ses (10, 20 and 40 mg/kg) orally for 10 days, followed by an intravenous injection at day 8 of either saline (10 mL/kg) or DOX (20 mg/kg). Hepatorenal toxicity was assessed by measuring the levels of serum creatinine (Cre), blood urea nitrogen (BUN), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP). The protein expression of 4-hydroxynonenal (4-HNE) in hepatorenal tissues was evaluated using immunohistochemistry. The malondialdehyde (MDA) content and antioxidant activity in the kidney and liver tissues were also measured. The results suggest that pretreatment with Ses ameliorated DOX-induced liver and kidney injury by lowering the serum ALT, AST, ALP, Cre and BUN levels ( p < 0.05 or p < 0.01), and the histological damage to the liver and kidney tissues induced by DOX compared to control were also significantly attenuated by Ses. Furthermore, Ses significantly decreased the DOX-induced increase of MDA and 4-HNE and increased the activity of CAT, SOD and GPX compared to the DOX-treated rats ( p < 0.05 or p < 0.01), whereas the change of DOX + Ses (10 mg/kg) group is not significant compared to the DOX-treated group ( p > 0.05). These findings indicate that Ses elicits a typical protective effect against DOX-induced acute hepatorenal toxicity via the suppression of oxidative stress.